2013
DOI: 10.1007/s10802-013-9799-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Mediates the Association Between ADHD and Depressive Symptoms in a Community Sample of Youth

Abstract: The purpose of this study was to examine the longitudinal relationship between attention-deficit/ hyperactivity disorder (ADHD) symptoms, emotion regulation (ER) ability, and depressive symptoms within a diverse community sample of 277 youth, ages 9–12 (56 % male). Participants were drawn from a larger study examining adolescent risk behaviors, and completed annual assessments over 3 years. Youth ADHD symptoms were assessed at Time 1 (T1) using the parent-reported Disruptive Behavior Disorders Rating Scale, ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 87 publications
7
69
2
1
Order By: Relevance
“…14 Many investigators measure ED among youth with ADHD using rating scales (e.g., Bunford et al 2014Bunford et al , 2015bSeymour et al 2012Seymour et al , 2014. Rating scales are appropriate for sampling a large number of situations (as opposed to a single experimental task) and can thus be representative of the multiple contexts of an individual's day.…”
Section: Rating Scalesmentioning
confidence: 99%
“…14 Many investigators measure ED among youth with ADHD using rating scales (e.g., Bunford et al 2014Bunford et al , 2015bSeymour et al 2012Seymour et al , 2014. Rating scales are appropriate for sampling a large number of situations (as opposed to a single experimental task) and can thus be representative of the multiple contexts of an individual's day.…”
Section: Rating Scalesmentioning
confidence: 99%
“…Using a cross-sectional design, results indicated that parent rated emotion regulation mediated the relationship between a diagnosis of ADHD and youth-reported ratings of depressive symptoms (Seymour, et al, 2012). Findings from their 2012 study subsequently were replicated using a longitudinal design (Seymour, et al, 2014). Youth between 9 and 12 years old were followed prospectively for 3 years, undergoing annual assessments.…”
Section: Explanations Concerning Etiological Relationships Though Almentioning
confidence: 98%
“…Reward responsivity and emotion regulation may be distal variables that predict both ADHD and depression (Anastopoulos et al, 2011;Meinzer et al, Unpublished manuscript;Seymour et al, 2012;Seymour et al, 2014), and thus focusing on reward responsivity and emotion regulation may reduce risk processes common to both disorders. Lack of family support may develop as a consequence of the turmoil (i.e., oppositional behavior, substance abuse, and academic failure) that many parents with a child with ADHD experience.…”
Section: Summary Research Overview and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations